Effect of verbascoside on apoptosis and metastasis in human oral squamous cell carcinoma. Issue 4 (16th April 2018) - Zhang, Yaqin; Yuan, Yi; Wu, Heming; Xie, Zhuoying; Wu, Yunong; Song, Xiaomeng; Wang, Jingjing; Shu, Wei; Xu, Junyong; Liu, Bin; Wan, Linzhong; Yan, Yanan; et al.
Abstract : Despite significant advances in therapy, the 5‐year survival rates for patients with advanced stage oral cancers still remains poor as an appropriate treatment has not been found yet, due to side effects of chemo/radiotherapy. Verbascoside (VB), a major bioactive constituent of the Tsoong herb, displays pharmacological properties by exhibiting anti‐oxidative, anti‐inflammatory and anti‐cancer activities. However, the underlining function and mechanism of VB in human oral squamous cell carcinoma (OSCC) remains unclear. In this study, we show that VB significantly decreased the viability and metastasis of HN4 and HN6 tumor cells, while promoting apoptosis. A xenograft OSCC mouse model further showed that intraperitoneal injection of VB strongly inhibited growth and lung metastasis of implanted tumor cells. Immunoblot analysis confirmed that VB effectively suppressed nuclear factor (NF)‐κB activation and downstream Bcl‐2/Bcl‐XL expression, resulting in increased OSCC cell apoptosis. In addition, VB suppressed mRNA and protein expression of matrix metalloproteinase‐9 via suppression of NF‐κB activation, thereby inhibiting tumor cell metastasis. Inspiringly, compared to cisplatin‐treated group, VB is a biocompatible agent without signficant side effects in vivo . Collectively, our results demonstrate that VB effectively inhibits OSCC tumor cell growth and metastasis via suppression of IκB kinase complex (IKK)/NF‐κB‐related signaling activation, suggesting that VB has potential use as a potent anticancer agent in OSCC therapeutic strategies. Abstract : What's new? The root of the Tsoong herb or C. cordifolioidea has been used as a herbal remedy in the Chinese Yunnan province since ancient times. Here the authors studied the effect of verbascoside, a major bioactive constituent of Tsoong, in human oral squamous cell carcinoma (OSCC). They find that verbascoside inhibited cell growth and promoted apoptosis in in vitro and in vivo models of OSCC by interfering with the activation of the transcription factor NF‐κB, pointing to a potential therapeutic function of verbascoside or Tsoong in OSCC patients.